Effects of fermentation length and varieties on the pasting properties of sour cassava starch - Adegunwa, M.O.; Sanni, Lateef O.; Maziya-Dixon, B.B. (International Society for Tropical Root Crops, 2012)
The effects of length of fermentation (5, 10, 15, 20 and 25 days) on pasting properties of sour starches produced from six cassava varieties were investigated. There were significant differences (p< 0.05) in pasting properties except pasting temperature and breakdown irrespective of the days of fermentation. Peak viscosity ranged from 308.50 to 466.63 RVA, trough ranged from 67.25 to 198.75 RVA, break down ranged from 147.71 to 320.25 RVA, final viscosity ranged from 100.29 to 233.00 RVA, set back ranged from 31.59 to 54.58 RVA, peak time ranged from 3.60 min to 4.06 min and pasting temperature ranged from 62.85 to 65.45 oC. Sour starches made from cassava TMS 30572, TMS 4(2) 1425 and 96/0603 recording the highest values. Sour cassava starch is used for making typical bread-like products such as “paodequeijo” in Brazil and “pandeyuca” in Colombia.